Fluorescent properties of some polythiophenes synthesized from 2‐(thiophen‐3‐yl)acetohydrazide and acetophenone. Issue 5 (22nd October 2020) - Linh, Nguyen Ngoc; Hung, Ha Manh; Oanh, Doan Thi Yen; Linh, Bui Thi Thuy; Cong, Nguyen Tien; Chinh, Nguyen Thuy; Hoang, Thai; Trung, Vu Quoc
Abstract: In this study, new polythiophenes containing hydrazone groups from derivatives of acetophenone were synthesized by chemical oxidative coupling polymerization. Ultraviolet‐visible spectroscopy (UV‐Vis) combined with infrared (IR) analyses proved the supposed structure of novel polythiophenes and proved conformance of the expected synthetic method. Morphology and surface properties of the synthesized polymers were investigated by field‐emission scanning electron microscopy (FE‐SEM). Thermal gravimetry analysis (TGA) has been reported that there was still the presence of small FeCl3 catalyst in polymers and polymers had a stable thermal stability under air atmosphere. The polymers displayed fluorescence emissions at about 590 nm attributed to the π‐conjugated polythiophene. Polymers without doping have a good electrical conductivity (around 4.03×10 –7 S/cm at 1 MHz).